Comparison of Methods for Determining Catchment Area Threshold for Water System Extraction - ZHENG Jiawei; CHEN Xingwei; LI Xiaocheng; RUAN Weifang (Renmin Zhujiang)
Most of the methods using digital elevation models (DEM) to extract water systems require the determination of catchment area thresholds.For a better understanding of the rationality and applicability of several commonly used determination methods of the catchment area threshold for water system extraction,the distance error between the real river source and the extracted one is used as a criterion to determine the rationality of the real water system extraction methods.Four main methods,namely,the drainage density method,the water-system fractal dimension method,the method of the minimum error at the river source,and the channel branching ratio method,are selected,and the Jinjiang River Basin on the southeast coast is taken as an example.The distance errors between the extracted river sources by different methods and the real river sources are compared.The results show that the visual discrimination of the catchment area threshold used by the drainage density method,water-system fractal dimension method,and channel branching ratio method has a large uncertainty,and the distance errors are large.In the method of the minimum error at the river source,the catchment area threshold is determined according to the minimum distance error between the extracted river source and the real one,which is unique.Hence,it is a more reasonable method among the four DEM-based real water system extraction methods.